Peculiarities of verbalization of the concept «Baiterek» in the national cultural consciousness. (Eurasian Journal of Philology Science and Education, 2015)
This paper attempts to research the concept of «Baiterek» and its actualization linguistic units. «Baiterek» is one of the basic concepts in Turkic, and in particular Kazakh linguistic world-image, which is ofgreat importance in the Kazakh mentality as a specific lingual personality and for the entire linguistic cultural community. Analysis of peculiarities of the implementation of the concept «Baiterek» enables identification of thegeneral and specific, collective and individual matters for the Kazakh linguistic consciousness.
Keywords: linguistic world-image; concept; free association experiment; national cultural consciousness